Pengaruh Belanja Desa Terhadap Kesejahteraan Masyarakat - Ari Hidayat; Sukma Mehilda; Decky Hendarsyah (FEB Universitas Sultan Ageng Tirtayasa, 2022)
The financial management and allocation of village finances are essential parts that cannot be separated from the village income and expenditure budget. The community's welfare is of great concern to the Government of the Republic of Indonesia, especially the welfare of the people in the village. This study aims to analyze the effect of village spending on community welfare. This study is a quantitative descriptive approach using primary data and secondary data with data collection techniques in the form of questionnaires and literature study. The sampling technique used random sampling with a total sample of 93 people. Simple linear regression, hypothesis testing, and coefficient of determination are being used to analyze the data. The study results show that village spending has a positive and significant effect on the welfare of rural communities. The results of this study assist the village government in allocating village expenditures, thereby providing a balanced proportion of village expenditures and following the needs of the village community, and ultimately improving the welfare of the village community.